2019
DOI: 10.1007/s10706-019-01035-4
|View full text |Cite
|
Sign up to set email alerts
|

Co-valorisation of Local Materials Tuffs and Dune Sands in Construction of Roads

Abstract: The main objective of this study is to enhance the performances of local materials in order to be used in road construction sector. To enhance the performances of this local materials, the strategy adopted is to combine the beneficial effects of mixing different materials and treatment using binders. The materials used in this study are tuffs and dune sands. Hence the present work is also a contribution to the covalorisation of local materials in arid region of the south of Algeria. According to the results ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 6 publications
0
9
0
Order By: Relevance
“…Mustapha et al [ 29 ] performed studies to improve the performance of local materials, such as tuffs and dune sands, for use in road construction. The results of their investigations showed that tuffs are suitable for base layers and foundations.…”
Section: Introductionmentioning
confidence: 99%
“…Mustapha et al [ 29 ] performed studies to improve the performance of local materials, such as tuffs and dune sands, for use in road construction. The results of their investigations showed that tuffs are suitable for base layers and foundations.…”
Section: Introductionmentioning
confidence: 99%
“…The results of the current study, particularly the maximum dry density and unconfined compressive strength have been compared with those of different studies undertaken on comparable materials. In the comparative study, the first results are related to studies conducted at another site in the Adrar region [15]. The second data set is relative to El Golea site [15].…”
Section: Comparison Of Present Results With Results Extracted From Di...mentioning
confidence: 99%
“…In the comparative study, the first results are related to studies conducted at another site in the Adrar region [15]. The second data set is relative to El Golea site [15]. The third data is relative to a study where a tuff is mixed with dune sands of Ouargla region [17].…”
Section: Comparison Of Present Results With Results Extracted From Di...mentioning
confidence: 99%
See 1 more Smart Citation
“…To improve the compactness, we opted for a correction of the particle size by substituting a fraction of (x %) of tuff by adding dune sand, with (x %) varying from 10 to 40. In order to find the optimum composition of the mixture, compaction and bearing tests were carried out on the different mixtures of tuffs and dune sands [24][25][26][27][28][29][30][31][32]. Simple compression tests at different ages were performed on specimens of different mixtures compacted at Modified Proctor Optimum (OPM).…”
Section: Optimal Formulationmentioning
confidence: 99%